Factors Affecting Quality of Profit in Indonesia Retail Trade Sub-sector Companies - Dwitama Putra, Yudha; Hermawan, Aditya (International Journal of Educational Research & Social Sciences, 2022)
This research was aimed to identify effects of profit growth, company size, and liquidity on profit quality. The population in this research was retail trade sub-sector companies which have been registered in Indonesian Stock Exchange in 2017-2020 by exerting purposive sampling technique. The total of research samples were about 14 companies. The type of research data was quantitative data and data source was secondary data with secondary data source. Meanwhile, the technique of data analysis was descriptive statistical analysis, classical assumption test, multiple regression analysis, determinant coefficient, and hypothesis test. The research result referred that profit growth, company size, and liquidity did not affect the profit quality.